2005
DOI: 10.1309/mgrxlqg9qvrvvmcg
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Initial and Deeper Sections of Esophageal Biopsy Specimens for Detection of Intestinal Metaplasia

Abstract: There are wide variations in the preparation of histologic sections from endoscopic esophageal biopsy specimens. We evaluated serial step sections from 261 esophageal or gastroesophageal junction biopsies at 4 levels to determine the first level at which goblet cell metaplasia (GCM) was detected. Deeper step sections of 152 paraffin blocks also were obtained to determine whether additional sections are useful in detecting GCM not seen in initial levels. GCM was identified in 95.3% of blocks in 3 levels. GCM wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…Different types of sections can be obtained from the tissue block based on the requirements.Serial sectioning is defined as obtaining a continuous ribbon of sections from a paraffin block & placing all the sections on multiple slides [7] .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Different types of sections can be obtained from the tissue block based on the requirements.Serial sectioning is defined as obtaining a continuous ribbon of sections from a paraffin block & placing all the sections on multiple slides [7] .…”
Section: Discussionmentioning
confidence: 99%
“…Incomplete sectioning through, a tissue block creates sampling error resulting in false negative diagnosis. In dermatopathology ,studies suggest that deeper levels provide more accurate diagnosis in one third of skin biopsies [1].The pathologist may require sections at different levels to be examined for final diagnosis and such situations necessitates the need for deeper sectioning [2].Despite the clear importance of diagnosing invasive or in situ skin cancer,few objective data exist to guide the dermatopathologist in deciding whether to examine additional step sections [3].In small biopsy specimens such as needle core and endoscopic biopsies deeper sectioning is routinely used in many laboratories to enhance sensitivity and diagnostic accuracy [4][5][6][7]. However, there are not many studies done and currently no standard methods are available to direct the performance of step sections .…”
Section: Introductionmentioning
confidence: 99%
“…When an initial section is non‐diagnostic, it is customary for the dermatopathologist to order one or more deeper/level sections (retrospective deeper sections), which may cause a delay in turn‐around‐time. To prevent this delay, some laboratories order deeper sections in advance for some or all biopsies (prospective deeper sections) . Because many biopsies do not require deeper sections, however, this leads to wasted time, cost and materials.…”
Section: Introductionmentioning
confidence: 99%
“…Prior studies have investigated the diagnostic utility of deeper sections in small specimens from a variety of organs, including the esophagus, colon, prostate, breast and cervix . In cutaneous specimens, research has been limited and has produced mixed results .…”
Section: Introductionmentioning
confidence: 99%
“…Chitkara et al took deep serial sections in addition to routine sectioning in cases assessed with H&E staining to detect Barrett's esophagus and investigated the presence of intestinal metaplasia that could not be observed initially. 18 Studies report that intestinal metaplasia is observed in deep sections (from the third to the eighth level) in 10.6% of patients in which intestinal metaplasia cannot be observed at the first level. Again, the same study detected intestinal metaplasia in deep sections in 12.5% of 32 patients documented as having Barrett's esophagus.…”
Section: Discussionmentioning
confidence: 99%